Overeducation at the start of the career: Stepping stone or trap? - Stijn Baert; Bart Cockx; Dieter Verhaest (Institute for the Study of Labor (IZA), 2012)
This study investigates whether young unemployed graduates who accept a job below their level of education accelerate or delay the transition into a job that matches their level of education. We adopt the Timing of Events approach to identify this dynamic treatment effect using monthly calendar data from a representative sample of Flemish (Belgian) youth who started searching for a job right after leaving formal education. We find that overeducation is a trap. This trap is especially important early in the unemployment spell. Our results are robust across various specifications and for two overeducation measures.
urn:nbn:de:101:1-201301213232
Keywords: C21; C41; I21; J24; J64; 330; overqualification; underemployment; school-to-work transitions; duration analysis; dynamic treatment; Berufseinstieg; Unterbeschäftigung; Erwerbsverlauf; Schätzung; Belgien